Expert drivers are better than non-expert drivers at rejecting unimportant information in static driving scenes. (November 2018) - Pammer, Kristen; Raineri, Alexandra; Beanland, Vanessa; Bell, Jason; Borzycki, Maria
Highlights: Core underlying cognitions/perceptions differ for expert drivers. Experts better than non-experts in detecting medium-threat objects. Experts worse than non-experts in detecting low-threat objects. Expert driving characterised by skill in rejecting unimportant information when driving. Implications for training novice drivers to develop core discrimination skills in driving. Abstract: Safe driving is predicated on a driver's ability to prioritise scene information to segregate hazards and potential hazards from other information, and allocate attention accordingly. Previous research has demonstrated that expert drivers are superior at detecting potential hazards when compared with non-expert drivers. However, hazard perception is a multi-faceted skill involving at least three components: drivers must look at the hazard, then detect it, and finally appraise it and respond appropriately. In the current study, we explored how expert drivers (paramedics, n = 151) and non-expert drivers ( n = 189) detect hazards of different threat value. To explore this question, we used a static, driving-related inattentional blindness (IB) task, in which an unexpected object in a critical trial varied from high threat (child running onto the road) to medium threat (pedestrian standing by the road) to low threat (garbage bin next to the road). We hypothesised that experts would have heightened awareness of hazards, which could be reflected as either generally higher rates of noticing objects in the driving scene (lower IB overall), or a heightened ability to prioritise the threat value of objects in the scene (lower IB for high threat, but not low threat objects). The results demonstrated that approx. 90% of drivers, irrespective of expertise, detected high threat objects placed on the side of the road. However, experts were more likely than non-experts to detect medium threat objects (55% of expert drivers vs. 40% of non-expert drivers), whereas the opposite pattern occurred for low threat objects (almost 20% of non-expert drivers noticed low-threat objects, compared with none of the expert drivers). We argue that expertise allows drivers to calibrate a hierarchy of attentional filtering to not only direct attentional resources to locations of interest, but also to explicitly prioritise objects of interest when driving. Importantly, this appears to be due to training rather than years of experience. These results point to the importance of not just increasing awareness while driving, but to develop discriminative capacity to filter out what is unimportant to facilitate safe driving.